CLINICOPATHOLOGICAL CORRELATION OF ANEMIA IN CHRONIC KIDNEY DISEASE: A CROSS-SECTIONAL STUDY IN A TERTIARY CARE HOSPITAL. - Dr. S Sivajyothsna; Dr . J Srikanth; Dr. D.S.S.K. Raju (Student's Journal of Health Research Africa, 2025)
Background